2012
DOI: 10.1007/s00210-011-0712-0
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and antioxidant effects of a single daily dose of sodium nitrite in a model of renovascular hypertension

Abstract: Dietary nitrite and nitrate have been reported as alternative sources of nitric oxide (NO). In this regard, we reported previously that sodium nitrite added to drinking water was able to exert antihypertensive effects in an experimental model of hypertension in a dose-dependent manner. Taking into consideration that nitrite is continuously converted to nitrate in the bloodstream, here we expanded our previous report and evaluate whether a single daily dose of sodium nitrite could exert antihypertensive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 37 publications
1
15
1
10
Order By: Relevance
“…Interestingly, it was shown that nitrite instillation in the jejunum decreased arterial blood pressure when NO-Hb achieved 10 mM concentration, and this was suggested as a level required for initiating vasorelaxation, even though the authors did not provide evidence that the hypotension was due to NO release from NO-Hb [42]. In addition, we found no significant increase in NO-Hb concentrations in rats treated with nitrite at 15 mg/kg for 4 weeks in a previous study [43]. Notwithstanding these criticisms, we believe that our findings are of major importance and very consistent.…”
Section: Discussioncontrasting
confidence: 59%
“…Interestingly, it was shown that nitrite instillation in the jejunum decreased arterial blood pressure when NO-Hb achieved 10 mM concentration, and this was suggested as a level required for initiating vasorelaxation, even though the authors did not provide evidence that the hypotension was due to NO release from NO-Hb [42]. In addition, we found no significant increase in NO-Hb concentrations in rats treated with nitrite at 15 mg/kg for 4 weeks in a previous study [43]. Notwithstanding these criticisms, we believe that our findings are of major importance and very consistent.…”
Section: Discussioncontrasting
confidence: 59%
“…Although antioxidant property of NaNO 2 at low doses has been reported, it does not act as a direct antioxidant. Montenegro et al [61] have shown the inability of nitrite to scavenge superoxide radicals or ameliorate iron-induced lipid peroxidation under in vitro conditions. The reported cellular antioxidant effect can probably be explained by NADPH oxidase downregulation and/or alterations in activities of enzymes involved in antioxidant defense [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite concentrations in the samples were determined using a previously described ozone-based reductive chemiluminescence assay [23]. First, saliva samples were diluted in ultrapure water, to obtain a 5% solution of stimulated whole saliva and 50% solution of submandibular and parotid saliva.…”
Section: Methodsmentioning
confidence: 99%